2017
DOI: 10.1016/j.nmni.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Propionimicrobium lymphophilum and Actinotignum schaalii bacteraemia: a case report

Abstract: Propionimicrobium lymphophilum is an anaerobic Gram-positive bacillus that exists in human skin and urinary tract. The pathogenicity is, however, not well known. Only two cases of urinary tract infection have been described recently. In the case presented here, the bacterium was isolated, concomitant with Actinotignum schaalii, from blood culture of a patient with fever and difficulty of urination. The bacteria were identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…This emerging opportunistic pathogen is supposed to be the causative agent of various types of infections linked to the urinary tract (Lotte et al, 2016 ). P. lymphophilum , reported as bacteraemia co-agent together with A. schaalii in the catheterized patient (Ikeda et al, 2017 ), was another uncommon species exclusively identified by PCR-DGGE-S. Because of simultaneous significant co-detection of these species ( p < 0.01, Fishers' test), we hypothesize their mutual relationship in the urinary tract. The role of uncommon bacteria is underestimated, in general, although they may significantly contribute to the pathophysiology and antimicrobial susceptibility pattern of CAUTI-associated biofilms as well as non-infective diagnoses (Shrestha et al, 2018 ).…”
Section: Discussionmentioning
confidence: 69%
“…This emerging opportunistic pathogen is supposed to be the causative agent of various types of infections linked to the urinary tract (Lotte et al, 2016 ). P. lymphophilum , reported as bacteraemia co-agent together with A. schaalii in the catheterized patient (Ikeda et al, 2017 ), was another uncommon species exclusively identified by PCR-DGGE-S. Because of simultaneous significant co-detection of these species ( p < 0.01, Fishers' test), we hypothesize their mutual relationship in the urinary tract. The role of uncommon bacteria is underestimated, in general, although they may significantly contribute to the pathophysiology and antimicrobial susceptibility pattern of CAUTI-associated biofilms as well as non-infective diagnoses (Shrestha et al, 2018 ).…”
Section: Discussionmentioning
confidence: 69%
“…The significant difference between As+ and As − samples’ β-diversity indicates that there are bacteria mutually exclusive/co-occurring to A. schaalii , as proved by many reports of poly-bacterial infections [ 5 , 6 , 7 , 8 , 9 , 10 ]. We identified P. lymphophilum and Fusobacterium nucleatum both separately and combined with Alcaligenes faecalis and Streptococcus spp.…”
Section: Discussionmentioning
confidence: 91%
“…Actinotignum schaalii is typically present in the urogenital tract and has not been detected in stool [3]. It has been recognized as an emerging, opportunistic pathogen and co-agent of various, typically polymicrobial infections [1,[4][5][6][7][8][9][10][11][12][13][14], easily overlooked due to its…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals infected by obligate or facultative anaerobic pathogens that are frequently undetected using typical urine culture diagnostic methods are present in cluster B-III (genera: 97au; individuals: 94au) (Imirzalioglu, et al, 2008). Of note, individual #116 was clinically diagnosed with UTI, and while a previous study reported Proteus mirabilis as the major UTI causing pathogen, ProteoStorm identified the rare UTI pathogen Propionimicrobium (1,129 out of 3,531 PSMs) (Ikeda, et al, 2017) as the most abundant genera followed by Facklamia (544 PSMs), Actinotignum (538 PSMs), Proteus (424 PSMs), and other gram-positive bacteria (Table S1).…”
mentioning
confidence: 93%